2008
DOI: 10.1017/s0033291707002681
|View full text |Cite
|
Sign up to set email alerts
|

Family history of depression is associated with younger age of onset in patients with recurrent depression

Abstract: FH of depression contributes to the onset of depression at a younger age and may affect the clinical features of the illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 44 publications
3
45
2
Order By: Relevance
“…While some negative findings have been reported [reviewed in Sullivan et al, 2000], most studies suggest an inverse relationship between AAO and familial risk, with the greatest risk observed in those under 30 years old. Two large clinical studies suggest that a family history of MDD is associated with an AAO of between 20 and 25 [Nierenberg et al, 2007;Tozzi et al, 2008]. In line with this, Lyons et al [1998] reported that while the heritability of early onset (<30) MDD was substantial (h 2 ¼ 0.70), estimates for later onset MDD (>30) were considerably lower (h 2 ¼ 0.10).…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…While some negative findings have been reported [reviewed in Sullivan et al, 2000], most studies suggest an inverse relationship between AAO and familial risk, with the greatest risk observed in those under 30 years old. Two large clinical studies suggest that a family history of MDD is associated with an AAO of between 20 and 25 [Nierenberg et al, 2007;Tozzi et al, 2008]. In line with this, Lyons et al [1998] reported that while the heritability of early onset (<30) MDD was substantial (h 2 ¼ 0.70), estimates for later onset MDD (>30) were considerably lower (h 2 ¼ 0.10).…”
Section: Introductionmentioning
confidence: 83%
“…The replication cohort consisted of two studies based in Munich, Germany: The Munich Antidepressant Response Signature (MARS) study [Ising et al, 2009;Kohli et al, 2011] and a clinical cohort of individuals collected in Munich [Tozzi et al, 2008]. The MARS study included 551 cases and 542 controls, and was designed as a pharmacogenetic study to monitor treatment response.…”
Section: Replicationmentioning
confidence: 99%
“…PGC would allow identifying SNPs of small effect and also testing, with reasonable power, the presence of genetic risk factors that predispose to MDD subtypes and to relevant symptom dimensions. Our study ascertained MDD cases with recurrent episodes reducing to some degree the substantial heterogeneity that exist for MDD; additional evidences however suggest that other clinical variables as severity 12 and age at onset 15,22 that appear to define more heritable phenotypes, should be considered for future analysis.…”
Section: Discussionmentioning
confidence: 99%
“…21 Approximately 26% of cases (n = 262) showed presence of at least one anxiety symptom during their worst episode as assessed by the SCAN interview. The anxiety symptoms considered were the presence of general rating of anxiety, general rating of phobia, free-floating anxiety or anxious foreboding with autonomic symptoms (see Tozzi et al, 2008 for more details on symptom selection). 22 Within patients with these anxiety symptoms 51% had a formal diagnosis of anxiety disorders (including generalized anxiety disorder, panic disorder with or without agoraphobia, social and specific phobia) according to DSM-IV.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation